Growth trends of spruce in the Orlické hory Mts. - M. Vejpustková; D. Zahradník; V. Šrámek; V. Fadrhonsová (Journal of Forest Science, 2004)
In 2002, height and diameter growth of spruce was investigated in the Orlické hory Mts. (the Czech Republic). The aim was to confirm and to quantify a growth increase in stands of different age, and to reveal the relation between growth and climate, and level of nitrogen deposition. Stem analyses of ten sample trees of mature spruce stand (average age 163 years) confirmed a significant increase in height and diameter growth since the mid-eighties of the 20th century. Nearly 75% of radial increment variability could be explained by climatic factors. Growth in the last 10 years corresponded well to weather conditions. Analysis of the growth - nitrogen deposition relationship showed negative correlations, but the results were not statistically significant. Comparison of the height growth curves of young stands (11-47 years) proved that the younger the stand, the steeper the growth curve. The height of the youngest stands was on average the double of the height of older stands at the same age. The values of the height growth of young stands significantly overreached the yield table values in all the age classes analyzed.